Psychosocial factors that influence marital couple duration - Sandu Mihaela Luminita,; Claudia Salceanu, (Technium Social Sciences Journal, 2021)
Humanity’s history, with its biological, psychological, social, cultural, economic and political dimensions, belongs to the coexistence of man and woman, to the relationships between them and their children. In time, family has become one of the oldest community forms, which ensures the evolution and continuity of the human species. Family influences the most the human being. Many studies made by researchers in this field, have proved the importance of the family for people, emphasizing that family is a real laboratory for the development of a person. In contemporary society, family suffered a lot of important transformations, like female empowerment for example, which, in turn, has determined many other changes in the family life. Due to these changes, the marital couple is currently more interested in satisfying its own interests and minimizes the tasks that society assigns to the family. A sample of 30 married couples, residing in Constanta County, has been assessed with Kansas Marital Satisfaction Scale, Locke-Wallace Marital Adjustment Scale, Kansas Marital Conflict Scale and Influence of the Material Situation on the Couple Questionnaire. The main objective of the research was to identify the relationship between these factors and the duration of the marital couple. We identified significant correlation between: (1) the couple’s duration and marital satisfaction; (2) the marital satisfaction and marital adjustment; (3) the level of the financial status and marital quarrels. Results are discussed in terms of marital counseling, the increase of marital satisfaction and the development of assistance for families in need.